2020
DOI: 10.3390/s20051539
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics Driven Diffusion Weighted Imaging Sensing Strategies for Zone-Level Prostate Cancer Sensing

Abstract: Prostate cancer is the most commonly diagnosed cancer in North American men; however, prognosis is relatively good given early diagnosis. This motivates the need for fast and reliable prostate cancer sensing. Diffusion weighted imaging (DWI) has gained traction in recent years as a fast non-invasive approach to cancer sensing. The most commonly used DWI sensing modality currently is apparent diffusion coefficient (ADC) imaging, with the recently introduced computed high-b value diffusion weighted imaging (CHB-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…Similar to our results, in this study, the differences originating from MRI acquisition were notably described as the most impactful on reliability ( 33 ), and only a few features showed good to excellent repeatability and reproducibility coefficients, although such identification is still insufficient for a reliable radiomics study ( 32 ). The observed reliability is poor also in other studies, in accordance with our results ( 34 , 35 ).…”
Section: Discussionsupporting
confidence: 91%
“…Similar to our results, in this study, the differences originating from MRI acquisition were notably described as the most impactful on reliability ( 33 ), and only a few features showed good to excellent repeatability and reproducibility coefficients, although such identification is still insufficient for a reliable radiomics study ( 32 ). The observed reliability is poor also in other studies, in accordance with our results ( 34 , 35 ).…”
Section: Discussionsupporting
confidence: 91%
“…Articles that studied radiomics in PCa are just briefly reminded and not analyzed in detail, and we had them incorporated in a table, along with their clinical outcomes and results. In PCa, the use of radiomics aids prostate volume selection and segmentation [ 30 , 40 , 46 , 73 , 74 , 75 , 76 ], PCa screening [ 28 , 77 , 78 ], detection and classification [ 29 , 77 , 79 , 80 , 81 ], in addition to its role in risk stratification [ 61 , 76 , 82 , 83 ], treatment [ 59 , 75 , 78 , 84 , 85 , 86 ], and prognosis. One of the first studies that analyzed the imaging features for PCA was performed by Khalvati et al [ 87 ], with the goal of creating a radiomics-based auto detection method utilizing an mpMRI feature model that combined computed high b-value DWI (diffusion-weighted imaging) and correlated diffusion imaging, which was then evaluated through a support vector machine (SVM) classifier.…”
Section: Resultsmentioning
confidence: 99%
“…Further study is warranted to assess whether DWI-driven radiomic signatures can predict 1-year LRF in patients with advanced HPSCC who want to receive OPT. Taken together, these findings suggest that a combination of image features through the analysis of CT images, MRI images (included DWI), and 18 F-FDG PET might provide enormous information about the tumor phenotypic features [40][41][42][43][44], and the aforementioned approach should be confirmed in future studies for patients with HPSCC who received CCRT for organ preservation.…”
Section: Discussionmentioning
confidence: 82%
“…Recently, Leithner et al reported that radiomic analysis derived from DWI imaging can provide high accuracy in subclassifying the molecular subtypes of breast cancer (luminals A and B, and HER2 enriched) [40]. Dulhanty et al also demonstrated that radiomics-driven DWI can be used as a forcefully sensing strategy to help physicians precisely screen zone-level prostate cancers for further targeted biopsy treatment [41]. Further study is warranted to assess whether DWI-driven radiomic signatures can predict 1-year LRF in patients with advanced HPSCC who want to receive OPT.…”
Section: Discussionmentioning
confidence: 99%